The effect of different statistical approaches on image quality data obtained from radiological examinations. Issue 2 (May 2022) - Saint, J.; England, A.; Mohammed Ali, A.; Bonnett, L.
Abstract: Introduction: Selection of optimal image acquisition protocols in medical imaging remains a grey area, the superimposed use of the Likert scale in radiological image quality evaluations creates an additional challenge for the statistical analysis of image quality data. Using a simulation study, we have trialled a novel approach to analysing radiological image quality Likert scale data. Methods: A simulation study was undertaken where simulated datasets were generated based on the distribution of Likert scale values according to varying image acquisition protocols from a real dataset. Simulated Likert scale values were pooled in four different ways; the mean, median, mode and the summation of patient Likert scale values of which the total was assigned a categorical Likert scale value. Estimates of bias, MAPE and RMSPE were then calculated for all four pooling approaches to determine which method most accurately represented an expert's opinion. Results: When compared to an expert's opinion, the method of summation and categorisation of Likert scale values was most accurate 49 times out of the 114 (43.0%) tests. The mean 28 times out of 114 (24.6%), the median 23 times out of 114 (20.2%) and the mode 17 times out of 114 (14.9%). Conclusion: We conclude that our method of summation and categorisation of Likert scale values is most often the best representation of the simulated data compared to the expert's opinion. Implications for practice: There is scope to reproduce this simulation study with multiple observers to reflect clinical reality more accurately with the dynamic nature of multiple observers. This also prompts future investigation into other anatomical areas, to see if the same methods produce similar results.